Barriers to unmet needs among mothers of children with disabilities in Kelantan, Malaysia: A qualitative study - Sukeri, Surianti; Bakar, Raishan S.; Othman, Azizah; Ibrahim, Mohd I. (Taibah University, Madinah, Kingdom of Saudi Arabia, 2017)
Objectives: The present study aimed to determine the barriers that deter mothers of children with disabilities from attaining their unmet needs. Methods: In-depth interviews of 12 mothers of children with disabilities were conducted from November 2014 to January 2015 in Kelantan, Malaysia. The mothers were recruited by purposive sampling. Thematic analysis was used for identifying, analysing and reporting the data. Results: Barriers to the unmet needs among mothers of children with disabilities were found to stem from the mothers’ expectation and further propagated by lack of support, the role of healthcare professionals in providing care, inappropriate policies and shortage of resources required for survival and maintaining care. Conclusions: Identification of the barriers to the attainment of unmet needs among mothers of disabled children is crucial for resolving the issue of unmet needs. Deeper understanding of these barriers may facilitate positive actions toward addressing the needs of these mothers and to alleviate the stress on mothers of disabled children. A concerted effort to coordinate services across all disciplines is required to dismantle these barriers by improving the provision of health care delivery and evaluation of welfare policies and services.